Spatial Planning Prerequisites for the Development of Affordable Housing in the Center of the City of Zagreb (Prostor, 2024)
This paper analyzes the concept of affordable housing and urban planning instruments that incentivize its development, especially in city centers. Considering the shortage of affordable housing in Zagreb, the research aims to identify contemporary urban planning practices that focus on the social function of housing and the role that local urban and housing policies have in ensuring access to it. By comparing the strategic documents for the housing development of the cities of Lyon and Barcelona and models of their implementation in the local urban plans for the areas of city centers and contact brownfield areas, the provisions incentivizing the development of the affordable housing (right of pre-emption, category of subsidized housing, inclusionary zoning, density bonus, and protection of residential use) are singled out. In the context of urban renewal of the historic center of Zagreb and of brownfield redevelopment in the contact zone of the city center, inclusion of the aforementioned provisions in local urban plans is examined, demonstrating the potential that such instrument has for the development of affordable housing in the city center.